The Eroding Spiritual Significance of Tarawangsa Art Among Teenagers - Fajar Ramadhan; Sri Wulandari; Dian Andriany (Siber Nusantara Research, 2026)
Culture is a way of life that develops and is shared by a group of people, which is passed down from generation to generation. Tarawangsa is one of these cultures and is a medium of cultural expression that contains traditional values that must be continuously preserved so that they are not lost to the times. However, with the development of the digital era and modern popular culture, the authenticity of the meaning and spiritual function of Tarawangsa has begun to erode, because the younger generation has easier access to global digital entertainment and less respect for traditional values. This study aims to understand the symbolic meaning of Tarawangsa art, analyze the younger generation's understanding of the symbolic meaning of Tarawangsa, and analyze the spiritual meaning in Tarawangsa that has been eroded in the younger generation. In this study, the method used is a descriptive qualitative method by conducting in-depth interviews with artists, namely Abah Abun and field observations to gather information about the younger generation's understanding of Tarawangsa art. Based on the analysis using Semiotic theory, Tarawangsa art has a deep meaning in the lives of Sundanese people. The results of the study indicate that the younger generation's understanding of the symbolic meaning of Tarawangsa is still limited and tends to be superficial.